Characteristics of coconut shell-based activated carbon as Ni and Pt catalyst supports for hydrotreating Calophyllum inophyllum oil into hydrocarbon-based biofuel. Issue 5 (October 2022) - Trisunaryanti, Wega; Wijaya, Karna; Triyono, Triyono; Wahyuningtyas, Nunung; Utami, Savira Putri; Larasati, Savitri
Abstract: Being massively produced as waste, coconut shell brings an excellent advantage to being a source of carbon for preparing a high-performing low-cost catalyst. In this study, the characteristics of coconut shell-based activated carbon (CSAC) prepared in different activation conditions were observed in its utilization as Ni and Pt catalyst supports for hydrotreating Calophyllum inophyllum oil (CIO) into hydrocarbon-based biofuel. Coconut shell waste was carbonized and activated at various conditions using two different strong base activating agents, NaOH and KOH, to produce numerous types of carbon supports. Amongst them, CSACK2–700 and CSACN3–700, displaying the highest surface area and the best adsorption capacity in the determination of iodine value, were selected to be loaded with two different metals to prepare hydrotreating catalysts: Pt metal for CSACN3–700 (Pt/CSACN3–700) and Ni for CSACK2–700 (Ni/CSACK2–700). The highest liquid product (84.77 wt%) with the best hydrocarbon selectivity (91 wt%) was obtained in the hydrotreatment of CIO at 550 ºC for 2 h using a 1:300 catalyst: feed weight ratio over well-dispersed Pt/CSACN3–700. Meanwhile, Ni/CSACK2–700 was only able to produce 78.83 wt% liquid yields containing 86.2 wt% hydrocarbons in its most optimum hydrotreatment condition using a 1:200 catalyst: feed weight ratio. In its repeated use, Pt/CSACN3–700 was shown to produce a consistent high-liquid product as opposed to Ni/CSACK2–700. However, an enhanced hydrocarbon selectivity was displayed by reusing Ni/CSACK2–700 for hydrotreatment. From the present study, a cost-effective and environmentally friendly alternative path to produce high-quality biofuel from the highly available Calophyllum inophyllum oil can be offered for future development. Graphical Abstract: ga1 Highlights: Coconut shell-activated carbon possessed micro-, meso-, and macropores. Strong based-activated coconut shell-based carbon exhibited high iodine number. Ni and Pt behave differently on the surface of coconut shell-based activated carbon. Metal-loaded coconut shell-based activated carbon was an effective hydrotreating catalyst for Calophyllum inophyllum oil. Coke deposition hindered the reusability of coconut-shell based activated carbon catalyst.